Mathematics

Question

(PLEASE HELP NEED ANSWER ASAP)
(PLEASE HELP NEED ANSWER ASAP)

1 Answer

  • Answer:

    C  a1= -2

        an = an-1 +3

    Step-by-step explanation:

    an = -2+ (n-1)3

    What is the first term?  Let n=1

    a1 = -2 + 0*3

    a1 = -2


    The difference between the  terms is +3  (coefficient on (n-1))

    The second term is the first term +3

    The third term is the second term plus 3

    The next term is the previous term +3

    so an = an-1+ 3

NEWS TODAY